Micronutrient Deficiency in Severe Preeclampsia - Akhter, Selina; Ali, Taskina; Begum, Shelina; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2013)
Background:. Micronutrient such as calcium, magnesium and zinc deficiency are associated with preeclampsia. Objective: To observe serum calcium, magnesium and zinc levels in severe preeclamptic women. Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka from July 2009 to June 2010. 60 cases of preeclampsia, aged 18-39 years and >20th weeks of pregnancy were included in the study group. They were further sub divided into group B1 (30 mild preeclampsia) and group B2 (30 severe preeclampsia). Age and gestational period matched 30 normotensive pregnant women (Group A) were also studied as control. All the preeclamptic women were selected from the Obstetric and Gynaecology in and out patient Department of BSMMU and Dhaka Medical College Hospital. Serum calcium and magnesium was measured by colorimetric and serum zinc was measured by spectrophotometric method. For statistical analysis one way ANOVA, independent sample t test and ÷2 test were used. Results: The mean serum calcium, magnesium and zinc levels were significantly (p<0.001) lower in both group of preeclampsia than normotensive pregnant women. Again serum calcium and zinc levels were significantly lower (P<0.05) in severe preeclampsia compared to mild preeclampsia whereas serum magnesium levels were found almost similar in both group of preeclampsia (P>0.05). Again in this study, 40% mild, 73.3 % severe preeclamptic women and 20% normotensive pregnant women had hypocalcaemia. 36.7% mild, 30.0% severe preeclamptic women and 3.3% normotensive pregnant women had hypomagnesaemia and 6.7% mild, 20 % severe preeclamptic women and no normotensive pregnant women had hypozincemia. Conclusion: This study may conclude that micronutrient deficiency may be one of the risk factor of preeclampsia and increases the risk of its severity. Therefore early detection and supplementation to treat this deficiency may reduce the incidence of preeclampsia. DOI: http://dx.doi.org/10.3329/jbsp.v8i1.16644 J Bangladesh Soc Physiol. 2013, June; 8(1): 26-32